CROSS-REACTIVITY OF COVID-19 IGG ASSAY WITH KNOWN IMMUNE-MEDIATED AND INFECTIOUS DISORDERS - Zehra, Nayab; khan, Muhammad Dilawar; Batool, Hijab; Chughtai, Omar Rasheed; Chughtai, Akhtar Sohail; Usman, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the cross-reactivity of COVID-19 IgG assay with known immune-mediated and infectious disorders and evaluate for any false-positive reactions to determine the specificity of the serological assay.Study Design: Cross-sectional analytical study.Place and Duration of Study: Department of Chemical Pathology, Chughtai Institute of Pathology, Lahore Pakistan, from Sep to Oct 2020.Methodology: A total of 116 samples were included in the study of both males and females. Diagnosed cases of typhoid fever, viral hepatitis, systemic lupus erythematosus (SLE), syphilis, multiple connective tissue disorders (MCTD), varicella-zoster infection, rabies, toxoplasmosis, epstein-barr virus (EBV) infection, rubella, rheumatoid arthritis, AIDS, cytomegalovirus (CMV) infection and dengue fever were included in the study. Three samples of multiparous women aged more than 40 years were also included in the study. IgG antibody levels were measured against SARS-CoV-2 with a cut-off index of 1.4.Results: Out of 116, only 3 (2%) samples were reactive for IgG against SARS-CoV-2. The categories showing cross-reactivity were typhoid, hepatitis C, and CMV. All specimens showing cross-reactivity were of females. Assay under consideration showed a specificity of 97.4%.Conclusion: Cross-reactivity was seen in pre-pandemic cases of infectious diseases with COVID-19 IgG antibody assay. Medical lab professionals must verify the serological assays before use in the clinical laboratory to avoid false-positive results.